Meningkatkan Keterampilan Memakai Baju Berkancing Melalui Media Model Bagi Anak Tunagrahita Ringan - Ega Yulanda; Irdamurni Irdamurni (Universitas Negeri Padang, 2019)
The research was motivated by the problems found in SLB Perwari Padang in class IV mentally retarded children. Of the two students experiencing problems in wearing buttoned clothes. In learning the teacher does the lecture method. To overcome this, researchers aim to improve the skills of wearing buttoned clothes to students through media models. The research method used is classroom action research consisting of II cycles. Each cycle consists of four meetings. The cycle is carried out in several stages, namely planning, action, observation and reflection. Data collection techniques are carried out, namely observation, documentation, and tests. The results of the study showed an increase in independence using buttoned clothes using media models for mild mentally retarded children. The results of the initial AL 30% ability test, Cycle I 49%, Cycle II 78%. Initial ability of JF 40%, Cycle I 75%, Cycle II 83%. It is recommended for the next teacher and researcher to use media models to improve skills using buttoned clothes for mild mentally retarded children.